1993
DOI: 10.1159/000236573
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Allergenic and Immunogenic Functions in Contact Sensitivity to Para-Phenylenediamine

Abstract: Contact sensitivity to para-phenylenediamine (PPD) is a frequent delayed-type hypersensitivity resulting in contact dermatitis. The aim of the present study, conducted in 16 patients allergic to PPD (as assessed by a positive patch test), was to get better insight into the mechanism of T-cell activation in PPD contact sensitivity. PPD was unable to induce significant proliferation of T cells from a first set of 9 patients. In 7 further patients, lymphocyte proliferation was assessed using PPD and 2 PPD metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 15 publications
2
59
3
Order By: Relevance
“…Of course, further investigations including skin testing are warranted to validate these results. Another surprising finding of this study was that we, in contrast to Krasteva et al [2], observed T cell-proliferative responses to PPD itself even in the absence of P450-modified antigens. The latter results were obtained on a polyclonal as well as on a monoclonal level.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Of course, further investigations including skin testing are warranted to validate these results. Another surprising finding of this study was that we, in contrast to Krasteva et al [2], observed T cell-proliferative responses to PPD itself even in the absence of P450-modified antigens. The latter results were obtained on a polyclonal as well as on a monoclonal level.…”
Section: Discussioncontrasting
confidence: 92%
“…Therefore, the balance between activation and/or detoxification processes is critical for immunogenic potentials of such compounds. PPD may be oxidized to Bandrowski’s base [ N,N′ -bis(4-aminophenyl)-2,5-diamino-1,4-quinone-diimine], which is involved in contact dermatitis to PPD [2]. We found that PPD is acetylated to monoacetyl-PPD (MAPPD) and to a lesser extent to N,N′ -diacetyl-PPD (DAPPD) in human skin and keratinocytes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat surprisingly, the chemical entity presented on MHC molecules to specific T-cell receptors in pPD-mediated contact sensitization is different to that which stimulates dendritic cell maturation. Early studies by Krasteva et al (1993) suggested that BB, but not pPD or primary oxidation products, stimulate T-cells from allergic patients. More recent studies with cloned T-cells suggest that both pPD and BB actually stimulate T-cells (Sieben et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is of course easy to classify potent allergens such as dichloronitrobenzene and chloromethylisothiazolinone, other chemicals may be rather weak allergens and the evidence that they do sensitize to any significant degree correspondingly inconclusive (e.g., octanol). Other materials, such as isoeugenol and p-phenylenediamine (PPD), are prohaptens, which are not chemically reactive agents but are rendered as such by metabolism in the skin (29,30). What all these substances have in common is that skin contact with the specific chemical can give rise to contact allergy.…”
Section: Discussionmentioning
confidence: 99%